Brain Gray Matter Atrophy and Functional Connectivity Remodeling in Patients With Chronic LHON - Tian, Qin; Wang, Ling; Zhang, Yu; Fan, Ke; Liang, Meng; Shi, Dapeng; Qin, Wen; Ding, Hao (Frontiers in Neuroscience, 2022)
To investigate the brain gray matter volume (GMV) and spontaneous functional connectivity changes in patients with chronic Leber’s hereditary optic neuropathy (LHON), and their relations with clinical measures. Thirty-two chronic LHON patients and matched sighted healthy controls (HC) underwent neuro-ophthalmologic examinations and multi-model MRI scans. Voxel-based morphometry (VBM) was used to detect the GMV differences between the LHON and HC. Furthermore, resting-state functional connectivity (FC) analysis using the VBM-identified clusters as seeds was carried out to detect potential functional reorganization in the LHON. Finally, the associations between the neuroimaging and clinical measures were performed. The average peripapillary retinal nerve fiber Layer (RNFL) thickness of the chronic LHON was significantly thinner (T=-16.421, P<0.001) and the mean defect of visual field was significantly higher (T = 11.28, P < 0.001) than the HC. VBM analysis demonstrated a significantly lower GMV of bilateral calcarine gyri in the LHON than the HC (P<0.05). Moreover, in comparison with the HC, the LHON had significantly lower FC between the centroid of the identified left calcarine gyrus and ipsilateral superior occipital gyrus, while higher FC between this cluster and the ipsilateral posterior cingulate gyrus (P<0.05, corrected). Finally, The GMV of the left calcarine gyrus was negatively correlated with the LHON duration (r=-0.535, P=0.002), and the FC between the left calcarine gyrus and the ipsilateral posterior cingulate gyrus of the LHON was negatively correlated with the average peripapillary RNFL thickness(r=-0.522, P=0.003). The atrophied primary visual cortex of the chronic LHON may be caused by trans-neuronal degeneration following the retinal damage. Moreover, our findings suggest that the functional organization of the atrophied primary visual cortex has been reshaped in the chronic LHON.